IFT88 maintains sensory function by localising signalling proteins along Drosophila cilia. - Werner, S.; Okenve-Ramos, P.; Hehlert, P.; Zitouni, S.; Priya, P.; Mendonça, S.; Sporbert, A.; Spalthoff, C.; Göpfert, M.C.; Jana, S.C.; Bettencourt-Dias, M. (Life science alliance, 2024)
Ciliary defects cause several ciliopathies, some of which have late onset, suggesting cilia are actively maintained. Still, we have a poor understanding of the mechanisms underlying their maintenance. Here, we show Drosophila melanogaster IFT88 (DmIFT88/nompB) continues to move along fully formed sensory cilia. We further identify Inactive, a TRPV channel subunit involved in Drosophila hearing and negative-gravitaxis behaviour, and a yet uncharacterised Drosophila Guanylyl Cyclase 2d (DmGucy2d/CG34357) as DmIFT88 cargoes. We also show DmIFT88 binding to the cyclase´s intracellular part, which is evolutionarily conserved and mutated in several degenerative retinal diseases, is important for the ciliary localisation of DmGucy2d. Finally, acute knockdown of both DmIFT88 and DmGucy2d in ciliated neurons of adult flies caused defects in the maintenance of cilium function, impairing hearing and negative-gravitaxis behaviour, but did not significantly affect ciliary ultrastructure. We conclude that the sensory ciliary function underlying hearing in the adult fly requires an active maintenance program which involves DmIFT88 and at least two of its signalling transmembrane cargoes, DmGucy2d and Inactive.